The Age of Angels: spiritualism and evolutionary progressionism in a nineteenth-century geologic time chart. (19th May 2018) - Monson, Charles C.
Abstract: The term 'Anthropocene' often carries apocalyptic overtones of environmental devastation, but many nineteenth-century iterations of the 'Age of Humans' idea were explicitly optimistic. The current time period was framed as a 'Psychozoic Era' or 'Age of Mind' in which human beings took their predetermined place at the pinnacle of 'creation'. Hiram Alvin Reid, an amateur scientist in the midwestern United States, took this line of thinking a step further. He drafted a geologic time chart in which the current 'Age of Man' was succeeded by a future 'Age of Angels', wherein humans will become higher beings. Reid was a Christian spiritualist who thought that evolution drove both physical and spiritual advancement, including the recent development of a 'sixth sense' that allowed humans to perceive ghosts and angels. Reid's views, while idiosyncratic and coloured by his metaphysical beliefs, drew heavily on mainstream concepts in biology and geology. Prominent geologists like James Dana and Joseph Le Conte argued for an Age of Mind in terms that mixed scientific rigor with religious and progressionist ideas. The Psychozoic was also embraced by many progressive-minded individuals outside the natural sciences, paralleling widespread modern interest in the Anthropocene.